Implementation Workshop of the Merdeka Curriculum for Elementary School Teachers in Pangandaran Regency - Rustini, Tin; Komariah, Komariah; Wahyuningsih, Yona; Dewi, Dini Anggraeni; Fujiyana, Annisa; Asti, Intan Surgani; Zahrana, Zona (Jurnal Pengabdian Masyarakat, 2023)
Purpose: This study investigates the implementation of the Merdeka Curriculum for elementary school teachers in Pangandaran Regency, emphasizing its significance in education. Method: Employing a qualitative approach and case studies, the research examines how teachers are using a contextual approach, local resources, and giving students freedom in learning. Challenges like inadequate training, limited resources, and administrative constraints are identified through thematic and descriptive analysis. Practical Applications: The research calls for the development of training and support programs to help teachers effectively implement the Merdeka Curriculum in primary schools. It also promotes a more adaptable educational approach in line with elementary students' needs. Conclusion: This study highlights the importance of addressing challenges in Merdeka Curriculum implementation and offers insights into improving the quality of education while making it more flexible for elementary students.